(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Breast cancer is a major ongoing public health issue among women in both developing and developed countries. The most common kind of breast cancer is adenocarcinoma, which includes invasive carcinoma and ductal carcinoma in situ (DCIS). A doctor can determine the stage of cancer based on the size of the tumour and if it has spread to the lymph nodes or other parts of the body. Breast Cancer Etiology Women must get general health tests to detect risk factors connected to an increased incidence of breast cancer development. Breast cancer risk factors may be classified into seven primary categories. Breast cancer epidemiology includes Breast cancer is the second-leading cause of cancer-related deaths among women worldwide, and it affects women more frequently than any other kind of cancer. Breast cancer was discovered in around 2.3 million females in 2020 and 685 000 individuals died as a result of the disease. It is critical that varied populations place a high priority on breast cancer prevention and control strategies. Raising awareness of risk factors and early detection is very critical in developing countries. As a rapidly developing field, nanotechnology brings promising opportunities to human cancer diagnosis and treatment. The use of nanoparticulate based platforms overcomes biological barriers and allows prolonged blood circulation time, simultaneous tumor targeting and enhanced accumulation of drugs in tumors. In this article authors have focused on various approach in diagnosis of breast cancer, as well as recent advancement in treatment of same using nanoparticles approach.